2002
DOI: 10.1038/415599b
|View full text |Cite
|
Sign up to set email alerts
|

Speech sounds learned by sleeping newborns

Abstract: It is not yet clear whether humans are able to learn while they are sleeping. Here we show that full-term human newborns can be taught to discriminate between similar vowel sounds when they are fast asleep. It is possible that such sleep training soon after birth could find application in clinical or educational situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(115 citation statements)
references
References 8 publications
5
106
2
2
Order By: Relevance
“…In a similar vein, the previous study by Kiviniemi et al (15) showed that low-frequency, spontaneous fMRI signal changes in the primary visual cortex persist during sedation in children. In addition, speech sounds have been found to be learned by sleeping newborns as indicated by electrophysiological responses (36). We could detect resting-state patterns in primary sensory regions (Figs.…”
Section: Discussionmentioning
confidence: 71%
“…In a similar vein, the previous study by Kiviniemi et al (15) showed that low-frequency, spontaneous fMRI signal changes in the primary visual cortex persist during sedation in children. In addition, speech sounds have been found to be learned by sleeping newborns as indicated by electrophysiological responses (36). We could detect resting-state patterns in primary sensory regions (Figs.…”
Section: Discussionmentioning
confidence: 71%
“…An oddball paradigm has been used to demonstrate that sleeping newborns are able to learn to discriminate small differences in speech sounds. The MMN-like activity was larger in a group of newborns that had received nocturnal stimulus training than in those that had not (Cheour et al, 2002b).…”
Section: Introductionmentioning
confidence: 90%
“…It was shown that a mismatch response was elicited both to changes in speech stimuli (e.g., Leppänen et al, 1999;Cheour et al, 2002b) and to changes in pure or complex tones (e.g., Leppänen et al, 1997;Čeponiene et al, 2002;Huotilainen et al, 2003). An oddball paradigm has been used to demonstrate that sleeping newborns are able to learn to discriminate small differences in speech sounds.…”
Section: Introductionmentioning
confidence: 99%
“…The MMN has been observed for both simple auditory discrimination, as well as relatively complex and even abstract regularities (20). Infants' MMRs can be measured from birth (21,22) and show a specific developmental pattern, beginning with a positive response in early infancy to a more mature negative-going MMN later on (23-25). Notably, MMN development is feature-specific; that is, an adult-like negativity may occur at different developmental times across various auditory features (23).…”
mentioning
confidence: 99%